2022
DOI: 10.5826/dpc.1203a115
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a topical formulation of Henna (Lawsonia inermis) on the itch and wound healing in patients with epidermolysis bullosa: A pilot single-arm clinical trial

Abstract: Introduction: Epidermolysis bullosa (EB) is a rare inherited genetic skin disorder with severe skin itching and recurrent blisters and erosion. There is no effective and specific therapy for all types of EB. Objective: The aim of this study was to evaluate a topical formulation of henna (Lawsonia inermis L.) in the management of wounds and the itching sensation in patients with EB. Methods: This is a pilot single-arm clinical trial. Nine patients with recessive dystrophic EB (RDEB), with the age ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Aligned with these results, a study found that Henna had protective effects in preventing and treating decubitus ulcers in critical care units (25). Another trial concluded that topical use of Henna is a practical treatment for epidermolysis bullosa by improving itching, burning, stringing, and cutaneous warmness sensation (26). It has been shown that Henna decreases epithelization time and accelerates wound contraction and healing by increasing collagen bands and fibroblasts and decreasing inflammatory cells (24,27).…”
Section: Discussionmentioning
confidence: 92%
“…Aligned with these results, a study found that Henna had protective effects in preventing and treating decubitus ulcers in critical care units (25). Another trial concluded that topical use of Henna is a practical treatment for epidermolysis bullosa by improving itching, burning, stringing, and cutaneous warmness sensation (26). It has been shown that Henna decreases epithelization time and accelerates wound contraction and healing by increasing collagen bands and fibroblasts and decreasing inflammatory cells (24,27).…”
Section: Discussionmentioning
confidence: 92%
“…The only study on henna included in this review assesses the satisfaction of the patient and the physician. They reported high levels of satisfaction and a significant improvement in itching, burning, local heat, and redness of the area ( p < 0.05), also in local pain, but not clinically significant [ 49 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“… Bias assessment by a one-to-one summary plot [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ]. …”
Section: Figurementioning
confidence: 99%